THE EFFECTS OF PERCEPTION ON PART TIME WORK AND LEARNING ACTIVITIES TOWARD ACADEMIC ACHIEVEMENT - Hidayat, Taupik (JOLADU: Journal of Language Education, 2022)
One of the most important thing for human life is education. It can develop human resource through teaching and learning activities. Higher education is an education level that is expected by many people. Those students do not only develop their intellectual, but they also need to have a mature social responsibility that they should always adjust to be advanced in various fields and is able to adapt to the society. It is a testament to the success of students which they need to achieve at the end of the learning process. The purposes of this study are: (1) Describing the effects of perception on part time work and learning activities toward the academi  achievement of colleg students of STIT Nusantara Bekasi and STKIP Albana Bekasi (2) Describing the effects of perception on part Time work toward the academic achievement of college students of STIT Nusantara Bekasi and STKIP Albana Bekasi. (3) Describing the effect of learning activities toward academic achievement majoring of college students of STIT Nusantara Bekasi and STKIP Albana Bekasi. To achieve the above purposes, the researcher uses quantitative research approach with descriptive research design. The instruments used are in the form of questionnaires. The test instrument is using validity and reliability. While the method of data analysis, the researcher uses multiple linear regression, with the number of respondents 65 students. The results of showed that: (1). There are any significant effects of perception on part time work and learning activities simultaneously toward the students’ academic achievement at private colleges in Bekasi City, it is proved by Sig value = 0,001 < 0,05 and F observed = 7.434 (2) There is a significant effect of perception on part time work towards the students’ academic achievement at private colleges in Bekasi city, it is proved by Sig value of 0,017 < 0,05 and the value of t observed = 2, 462 (3) There is a significant effect of learning activities towards the students’ academic achievement at private colleges in Bekasi city, by Sig value of 0,006 < 0,05 and t observed = 2,876